Fine‐Scale Movement Data Reveal Primarily Surface Foraging and Nocturnal Flight Activity in the Endangered Bermuda Petrel - Paolo Becciu; Allison Patterson; Carina Gjerdrum; Jeremy Madeiros; Letizia Campioni (Ecology and Evolution)
ABSTRACT Foraging behaviour plays a fundamental role in animal fitness and population dynamics., particularly for central‐place foragers like breeding seabirds. Among Procellariiform seabirds, petrels exhibit a wide range of foraging strategies finely tuned to the patchy and unpredictable distribution of resources. The extent and remote nature of their foraging grounds makes direct observation of foraging behaviour impractical, thereby requiring the use of remote tracking technologies. We deployed miniaturised multi‐sensor biologgers and collected fine scale movement data to investigate the at‐sea behaviours of the Bermuda petrel Pterodroma cahow, a poorly studied and highly threatened gadfly petrel, specialised on mesopelagic prey. GPS‐tracking data revealed extensive foraging trips (mean ± SD: 1207 ± 305 km), in consistent directions, over remote oceanic regions. Time‐depth‐recorders provided new insights into Bermuda petrel feeding techniques suggesting that the meso‐bathypelagic prey targeted by petrels must be available in the very upper layer of the water surface, given their very limited diving activity (maximum dive depth of 1.57 m). We identified three flight‐related and three water‐associated behaviours using supervised classification approach to classify behaviour from tri‐axial acceleromtetry. Flying behaviours reflected the expected dynamic soaring flight strategy of Procellariiformes; individuals spent more than 75% of their time in flight (dynamic soaring and flap‐gliding) with dynamic soaring flight being the most common behaviour under all conditions. The behaviour classified as ‘Intensive flight’ was infrequently observed but could indicate aerial dipping, a characteristic foraging technique of Pterodroma species. The remaining time was spent in three water behaviours: active, inactive and intensive, with the latter being less common but thought to reflect scavenging and prey seizing. Flight increased during dusk and in the night, highlighting greater flight activity during night compared to the day, while water behaviours were more common during the day. While some of our findings may require further validation to confirm their relevance to foraging behaviour, our work offers new and valuable insights to consider when assessing the ecological needs of this endangered species and its potential vulnerability to offshore anthropogenic activities.